An analysis of factors affecting the efficiency of gains in pigs from birth to weaning - Bonsma, J. (Not identified, 2022)
Although many considerations are involved in raising hogs economically, it can be safely said that the food required to produce a unit of gain in the live weight . on the suckling pig represents the greatest portion of the entire cost of production up to weaning time. Thus food consumption per unit of gain is closely associated with the success or failure of a hog enterprise. Several workers (1 and 2) have found that 76% to 84% of the cost of producing a market hog is made up of feed cost. Those factors which tend to increase the feed required to produce a pound of gain in the suckling pigs will increase the cost of producing a weanling pig and also a market hog. In the present investigation consideration is given to various conditions which influence the amount of feed consumed by suckling pigs to produce a pound of gain in live weight from birth to weaning time.